Intestinal barrier function is maintained with aging – a comprehensive study in healthy subjects and irritable bowel syndrome patients - Wilms, Ellen (Sci Rep, 2020)
Animal studies have shown that intestinal barrier function is compromised with aging. We aimed to assess the effects of aging on intestinal barrier function in humans in vivo and ex vivo. In this cross-sectional study, healthy subjects and subjects with irritable bowel syndrome (IBS) of older (65–75 years) and young adult age (18–40 years) were compared. In vivo gastrointestinal site-specific permeability was assessed by a multi-sugar test, taking into account potential confounders. Sigmoid biopsies were collected from subgroups of healthy young adults and elderly for ex vivo Ussing chamber experiments, gene transcription of barrier-related genes and staining of junctional proteins. No significant differences between healthy young adults and elderly were found for small intestinal, colonic and whole gut permeability (P ≥ 0.142). In IBS patients, gastroduodenal and colonic permeability did not differ significantly (P ≥ 0.400), but small intestinal and whole gut permeability were higher in elderly versus young adults (P ≤ 0.009), mainly driven by the IBS-diarrhea subtype. Ussing chamber experiments with or without stressor (P ≥ 0.052), and relative expression of intestinal barrier-related genes (P ≥ 0.264) showed no significant differences between healthy elderly and young adults, as confirmed by immunofluorescent stainings. Overall, the functional capacity of the intestinal barrier is maintained in elderly.